(untitled) - Papadopoulos, Apostolos N. (New York, NY, 2005)
This monograph explores the way spatial database management systems aim at supporting queries that involve the space characteristics of the underlying data, and discusses query processing techniques for nearest neighbor queries. It provides both basic concepts and state-of-the-art results in spatial databases and parallel processing research, and studies numerous applications of nearest neighbor queries.
Phân tích thiết kế giải thuật nâng cao
Keywords: Quản lý dữ liệu,Database management